How do elite endurance runners alter movements of the spine and pelvis as running speed increases? - Preece, S. J.; Mason, D.; Bramah, C. (Gait and Posture, 2016)
Elite endurance runners are characterised by their performance ability and higher running economy. However, there is relatively little research aimed at identifying the biomechanical characteristics of this group. This study aimed to understand how motions of the pelvis, lumbar spine and thorax change with speed in a cohort of elite endurance runners (n = 14) and a cohort of recreational runners (n = 14). Kinematic data were collected during over ground running at four speeds ranging from 3.3 to 5.6 m s-1 and a linear mixed model used to understand the effect of speed on both range of motion and mean sagittal inclination. The results showed the two groups to exhibit similar changes in range of motion as speed was increased, with the most pronounced increases being observed in the transverse plane. However, the adaptation of thorax inclination with speed differed between the two groups. Whereas the recreational runners increased thorax inclination as running speed was increased, elite endurance runners consistently maintained a more upright thorax position. This is the first study to identify specific differences in upper body motions between recreational and elite runners and the findings may have implications for training protocols aimed at improving running performance.